3D-printed scaffolds with carbon nanotubes for bone tissue engineering: Fast and homogeneous one-step functionalization. (15th July 2020) - Liu, Xifeng; George, Matthew N.; Park, Sungjo; Miller II, A. Lee; Gaihre, Bipin; Li, Linli; Waletzki, Brian E.; Terzic, Andre; Yaszemski, Michael J.; Lu, Lichun
Abstract: Three-dimensional (3D) printing is a promising technology for tissue engineering. However, 3D-printing methods are limited in their ability to produce desired microscale features or electrochemical properties in support of robust cell adhesion, proliferation, and differentiation. This study addresses this deficiency by proposing an integrated, one-step, method to increase the cytocompatibility of 3D-printed scaffolds through functionalization leveraging conductive carbon nanotubes (CNTs). To this end, CNTs were first sonicated with water-soluble single-stranded deoxyribonucleic acid (ssDNA) to generate a negatively charged ssDNA@CNT nano-complex. Concomitantly, 3D-printed poly(propylene fumarate) (PPF) scaffolds were ammonolyzed to introduce free amine groups, which can take on a positive surface charge in water. The ssDNA@CNT nano-complex was then applied to 3D-printed scaffolds through a simple one-step coating utilizing electric-static force. This fast and facile functionalization step resulted in a homogenous and non-toxic coating of CNTs to the surface, which significantly improved the adhesion, proliferation, and differentiation of pre-osteoblast cells. In addition, the CNT based conductive coating layer enabled modulation of cell behavior through electrical stimuli (ES) leading to cellular proliferation and osteogenic gene marker expression, including alkaline phosphatase (ALP), osteocalcin (OCN), and osteopontin (OPN). Collectively, these data provide the foundation for a one-step functionalization method for simple, fast, and effective functionalization of 3D printed scaffolds that support enhanced cell adhesion, proliferation, and differentiation, especially when employed in conjunction with ES. Statement of Significance: Three-dimensional (3D) printing is a promising technology for tissue engineering. However, 3D-printing methods have limited ability to produce desired features or electrochemical properties in support of robust cell behavior. To address this deficiency, the current study proposed an integrated, one-step method to increase the cytocompatibility of 3D-printed scaffolds through functionalization leveraging conductive carbon nanotubes (CNTs). This fast and facile functionalization resulted in a homogenous and non-toxic coating of CNTs to the surface, which significantly improved the adhesion, proliferation, and differentiation of cells on the 3D-printed scaffolds. Graphical abstract: Image, graphical abstract